Mengintegrasikan Aspek-Aspek Kebudayaan Arab dalam Pembelajaran Bahasa Arab - Syakira Esa Rahimi Sari; Sangidu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In this paper, literature, history, art, and cultural values ​​are discussed and it is emphasized that Arabic does not only function as a means of communication, but also a reflection of the culture and way of life of Arab society. The lack of ability of Arab teachers in understanding Arabic culture which results in difficulties in the learning process that integrates aspects of Arabic culture is an important factor in the decline in students' mastery and understanding of the technical aspects of the language, both meaning and broader cultural context. So the purpose of cultural integration in the Arabic language learning curriculum is to gain a deeper and contextual understanding of the language, social, history, and cultural values ​​that exist in the language. With the theory of cultural integration using qualitative descriptive methods used in this study, which involved observation, in-depth interviews, and document analysis, revealed. The results showed that higher learning motivation, improved language skills and a deep understanding of Arabic culture can enrich students' learning experiences and prepare them to interact better in the international world. This study shows that culture-based teaching methods are more effective when used in the Arabic language learning process. However, the main problem for teachers who do not understand Arabic culture, which requires strategic solutions such as the use of technology and special training. With the aim of improving teaching efficiency and students' understanding of Arabic language and its culture as a whole, this paper provides practical guidelines for educators to incorporate Arabic cultural elements into the Arabic language learning process.